FONi's Performances in the Hydroponic Cultivation of Various Vegetables - Eka Erfiana; Budi Indra Setiawan; Satyanto Krido Saptomo (PERTETA, 2025)
Land conversion, a phenomenon being encountered today, has led to a decline in the availability of agricultural land. On the other hand, population growth requires more food, which means more farmland is needed. Hydroponics is a method to grow crops intensively in any form of space without using soil, but only nutritious water as the growing medium. Hydroponics can produce high-quality crops and is easy to implement, making it popular in urban areas. However, it requires a continuous flow of water using electric pumps, which ultimately increases investment and operating costs. In this study, FONi (An Unpowered Automatic Fertigator) was tested to maintain water levels and flow rates as required by the plants. FONi is designed to replace the water lost by plant evapotranspiration, utilizing an automatic water valve. Here, FONi demonstrated good performance in growing three types of vegetables, namely water spinach (kangkung), choy sum (caisim), and spinach (bayam). The water productivity of each was 47.51 kg/m³, 43.80 kg/m³, and 21.25 kg/m³, respectively, and the land productivity was 1.35 kg/m², 0.97 kg/m², and 0.57 kg/m², respectively. The overall water efficiency was above 80%. By applying FONi, hydroponic cultivation activities at the research site, which had been suspended, can resume without incurring electricity costs.